The ecosystem approach in ocean planning and governance : perspectives from Europe and beyond - Langlet, David; Rayfuse, Rosemary Gail (Publications on ocean development ;, 2019)
The Ecosystem Approach in Ocean Planning and Governance takes stock of the challenges associated with implementing an ecosystem approach in ocean governance. In addition to theorizing the notion of Ecosystem Approach and its multifaceted implications, the book provides in depth analyses of lessons learned and remaining challenges associated with making the Ecosystem Approach fully relevant and operational in different marine policy fields, including marine spatial planning, fisheries, and biodiversity protection. In doing so, it adds much needed legal and social science perspectives to the existing literature on the Ecosystem Approach in relation to the marine environment. While focusing predominantly on the European context, the perspective is enriched by analyses from other jurisdictions, including the USA.